Asiaticoside Combined With Carbon Ion Implantation to Improve the Biocompatibility of Silicone Rubber and to Reduce the Risk of Capsule Contracture - Liu, Xing; Song, Ya-Jun; Chen, Xing; Huang, Meng-Ya; Zhao, Chen-Xi; Zhou, Xun; Zhou, Xin (Frontiers in Bioengineering and Biotechnology, 2022)
Capsular contracture caused by silicone rubber is a critical issue in plastic surgery that urgently needs to be solved. Studies have shown that carbon ion implant in silicone rubber (carbon silicone rubber, C-SR) can significantly improve the capsular structure, but the effect of this improvement only appear two months or later. In this study, asiaticoside combined with carbon silicone rubber was used to explore the changes in the capsule to provide a reference for the treatment of capsule contracture. Human fibroblasts (HFF-1) were used for in vitro experiments. The combined effect of asiaticoside and carbon silicone rubber on cell proliferation was determined by the CCK8 method, cell migration changes were measured by Transwell assays, cell cycle changes were measured by flow cytometry, and the expression levels of fibroblast transformation markers (vimentin and α-SMA), collagen (Col-1A1) and TGF-β/Smad signaling pathway-related proteins (TGF-β1, TβRI, TβRII and Smad2/3) were detected by immunofluorescence. In vivo experiments were carried out by subcutaneous implantation of the material in SD rats, and asiaticoside was oral administered simultaneously. WB and ELISA were used to detect changes in the expression of TGF-β/Smad signaling pathway-related proteins. TGF-β/Smad signaling pathway proteins were then detected and confirmed by HE, Masson and immunohistochemical staining. The results shown that asiaticoside combined with carbon ion implantation inhibited the viability, proliferation and migration of fibroblasts on silicone rubber. In vitro immunofluorescence showed that the secretion levels of α-SMA and Col-1A1 were significantly decreased, the transformation of fibroblasts into myofibroblasts was weakened, and the TGF-β/Smad signaling pathway was inhibited. In vivo experimental results showed that asiaticoside combined with carbon silicone rubber inhibited TGF-β1 secretion and inhibited the TGF-β/Smad signaling pathway, reducing the thickness of the capsule and collagen deposition. These results imply that carbon silicone rubber combined with asiaticoside can regulate the viability, proliferation and migration of fibroblasts by inhibiting the TGF-β/Smad signaling pathway and reduce capsule thickness and collagen deposition, which greatly reduces the incidence of capsule contracture.